VOCs catalytic oxidation catalyst as well as preparation method and application thereof
By using cheap natural clay minerals as templates, combined with non-precious metal salt solution impregnation and alkali etching, a VOCs catalytic oxidation catalyst with porous structure was prepared, which solved the problem of low pollution and application value of catalyst preparation in the prior art, and achieved excellent performance and simple preparation of catalysts.
Patent Information
- Application Number
- CN202311326617.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, the preparation of catalysts using colloidal crystal template method and hydrothermal synthesis method has problems such as pollution, difficulty in industrial amplification and low application value, resulting in the unmet need to develop VOCs catalytic oxidation catalysts containing non-precious metals with excellent performance and simple preparation.
Using cheap natural clay minerals as templates, a porous VOCs catalytic oxidation catalyst was prepared by impregnation with a non-precious metal salt solution, first drying and first calcination, and then etching the catalyst precursor with alkali.
The prepared catalyst has a high specific surface area and rich pore structure, excellent performance than catalytic oxidation of VOCs, and the preparation process is simple, making it suitable for industrial applications.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to a VOCs catalytic oxidation catalyst, and in particular to a porous VOCs catalytic oxidation catalyst prepared using a cheap natural clay mineral as a template, as well as a preparation method of the catalyst and application of the catalyst in catalytic oxidation treatment of VOCs. Background Art
[0002] Air pollution is receiving increasing attention. A series of regulations and systems have been introduced to limit the emission of volatile organic compounds (VOCs). Common VOCs treatment methods include adsorption, absorption, membrane separation, catalytic oxidation, electrochemical treatment, etc. The catalytic oxidation method is to make VOCs burn flamelessly at a lower ignition temperature in the presence of a catalyst, completely decompose into carbon dioxide and water, and release heat. The catalysts used can be divided into two categories according to the active components: precious metal catalysts and non-precious metal catalysts. Catalysts using precious metals such as Pt, Pd, Rh, and Ir have been successfully industrialized for many years. They have the characteristics of low ignition and complete combustion temperatures and a wide range of applications, but they have the disadvantages of being expensive and easy to be poisoned. Catalysts using non-precious metals such as Cu, Co, Fe, Mn, Ce, etc. are relatively low in price, have variable metal valence states, and are good in resistance to poisoning. In addition, the structure of the catalyst is one of the important factors affecting the performance of the catalyst. The catalytic oxidation process of VOCs molecules passing through the catalyst includes attachment to the catalyst surface, neutralization, conversion, and product separation. Therefore, catalysts with higher specific surface area and more abundant pores will facilitate VOCs molecules to attach to the catalyst surface or in the pores, undergo conversion, and discharge products (i.e., CO2 and H2O). Therefore, the development of porous catalysts has a wide range of applications and economic value for the catalytic oxidation of VOCs.
[0003] Feng et al. (Feng N, Chen C, Meng J, et al. K-Mn supported on three-dimensionally ordered macroporous La 0.8 Ce 0.2 FeO3 catalysts for the catalytic combustion of soot[J].Applied Surface Science,2017,399:114-122.) Ordered macroporous La was successfully synthesized by colloidal crystal template method. 0.8 Ce 0.2 FeO3 perovskite, and the perovskite surface was successfully modified by using K and Mn to form K2Mn4O8, which increased the concentration of surface oxygen species and improved the reducibility of the catalyst, thereby significantly improving the catalytic activity of catalytic combustion of soot.
[0004] Chinese patent CN113477252A discloses a preparation method and application of a composite porous catalyst containing titanium and other transition metals. It adopts a hydrothermal synthesis method to synthesize a metal composite material TiSiMOx with a high specific surface area and large mesopore volume, wherein M is Fe, Co, Ni, Cu, and Zn. The metal composite material contains both zeolite phase and other oxide phases, and has excellent catalytic oxidation properties.
[0005] In the prior art, a colloidal crystal template method is used to prepare a catalyst. This method pollutes the environment during the preparation process, is difficult to scale up industrially, and has low application value. In the prior art, a hydrothermal synthesis method is also proposed to prepare a catalyst. This method also has the problem of being difficult to scale up industrially and having low application value.
[0006] Therefore, there has always been a need to develop non-precious metal-containing VOCs catalytic oxidation catalysts with excellent performance and simple preparation. Summary of the invention
[0007] The present invention aims at the problem that the activity of VOCs catalytic oxidation catalyst containing non-precious metals is not high, and provides a VOCs catalytic oxidation catalyst, a preparation method and application thereof. The catalyst of the present invention is a porous VOCs catalytic oxidation catalyst prepared by using a low-cost and easily available clay mineral as a template. The catalyst of the present invention has a high specific surface area and abundant pores, and therefore has excellent performance in catalytic oxidation of VOCs.
[0008] The inventors unexpectedly discovered that a porous catalyst with a high surface area, abundant pores and a special morphology can be prepared by using pretreated clay minerals as templates. The catalyst has excellent performance in catalytic oxidation of VOCs. Thus, the present invention was completed.
[0009] Therefore, in one aspect, the present invention provides a method for preparing a VOCs catalytic oxidation catalyst, comprising the following steps:
[0010] impregnating a clay mineral with a non-precious metal salt solution, and performing a first drying and a first calcination on the impregnated product to obtain a catalyst precursor, wherein the amount of the clay mineral is 0.1-30wt%, preferably 1-20wt%, and more preferably 5-15wt% of the non-precious metal salt solution; and
[0011] The catalyst precursor is etched with alkali to remove at least part of the clay minerals in the catalyst precursor to obtain a VOCs catalytic oxidation catalyst.
[0012] In one aspect, the present invention provides a VOCs catalytic oxidation catalyst prepared by the above method.
[0013] In one aspect, the present invention provides use of the above-mentioned VOCs catalytic oxidation catalyst in the catalytic oxidation of VOCs.
[0014] Compared with the VOCs catalytic oxidation catalyst in the prior art, the VOCs catalytic oxidation catalyst prepared by the method of the present invention has the advantages of simple preparation, high specific surface area and excellent performance in catalytic oxidation of VOCs. DETAILED DESCRIPTION
[0015] In this document, unless otherwise expressly stated, all percentages and contents are by weight.
[0016] Except in the examples, all numerical values of parameters herein are to be understood as being modified in all instances by the term "about", whether or not "about" actually appears before the numerical value.
[0017] In one embodiment, the present invention provides a method for preparing a VOCs catalytic oxidation catalyst, which comprises the following steps:
[0018] impregnating a clay mineral with a non-precious metal salt solution, and performing a first drying and a first calcination on the impregnated product to obtain a catalyst precursor, wherein the amount of the clay mineral is 0.1-30wt%, preferably 1-20wt%, and more preferably 5-15wt% of the non-precious metal salt solution; and
[0019] The catalyst precursor is etched with alkali to remove at least part of the clay minerals in the catalyst precursor to obtain a VOCs catalytic oxidation catalyst.
[0020] The present invention has no particular limitation on the impregnation, and conventional means in the art may be used. In one variation, the impregnation is performed for 10-120 min, preferably 20-60 min.
[0021] In one embodiment, the clay mineral is one or more selected from montmorillonite, saponite, diatomite, kaolin, talc, illite, vermiculite, sepiolite, attapulgite, and serpentine, preferably one or more selected from montmorillonite, diatomite, kaolin, and attapulgite.
[0022] In one embodiment, the clay mineral may be pretreated. The pretreatment may be one or more of pickling, alkali washing, and heat treatment, preferably one or both of pickling and heat treatment. The acid may be one selected from hydrochloric acid, sulfuric acid, and nitric acid. In one variation, the acid is used in an aqueous solution with a concentration of 0.1-10 mol / L, preferably 0.5-8 mol / L, and more preferably 1-6 mol / L. Pickling may be performed for 0.5-8 hours. In one variation, the heat treatment is performed at 200-900°C, preferably 300-700°C, for 1-12 hours, preferably 2-8 hours.
[0023] In one embodiment, the non-precious metal may be one or more selected from Cu, Co, Fe, Mn, Ce, Zr, La, Mg, Ti, Li, Na, K, Rb, Cs, Ca, Ba, Sr, Cr, Mo, W, Ni, Re, Zn, Cr, Ga, Al, Sn. The non-precious metal salt may be a nitrate, sulfate or hydrochloride of the above non-precious metal. In one variation, the non-precious metal salt is a nitrate of one or more non-precious metals selected from Cu, Co, Mn, Ce, and Zr. In one variation, the concentration of the non-precious metal salt solution is 0.01-5 mol / L, preferably 0.05-3 mol / L, and more preferably 0.08-1 mol / L.
[0024] In one embodiment, the first drying is performed at 60-150° C. for 2-48 hours.
[0025] In one embodiment, the first calcination is performed at 300-700° C., preferably 450-600° C., for 1-12 hours, preferably 2-8 hours.
[0026] In one embodiment, the base is one or more selected from lithium hydroxide, sodium hydroxide, potassium hydroxide, and calcium hydroxide, preferably sodium hydroxide, potassium hydroxide, or both. In a variation, the base is used in an aqueous solution with a concentration of 0.1-10 mol / L, preferably 0.5-8 mol / L, and more preferably 1-6 mol / L.
[0027] In one embodiment, the etching of the catalyst precursor with alkali comprises the following steps: mixing the catalyst precursor with the aqueous solution of the alkali in a water bath, stirring for 2-12 hours, and centrifuging to obtain a solid, washing, second drying and optional second calcination to obtain the VOCs catalytic oxidation catalyst. In a variation, stirring is performed at a temperature of 50-95°C for 2-12 hours. In a variation, the second drying is performed at 60-150°C for 2-48 hours. In a variation, if the second calcination is performed, it is performed at 300-700°C, preferably 450-600°C.
[0028] In one aspect, the present invention provides a VOCs catalytic oxidation catalyst prepared by the above method. In one embodiment, the VOCs catalytic oxidation catalyst is a porous structure and has a plurality of mesoporous channels. In this article, the term "mesopore" refers to a pore with an average pore size of 2-50nm. The presence of mesoporous channels helps VOCs molecules and reaction product molecules to enter and exit the catalyst, thereby helping to improve the catalytic performance. In one variation, the VOCs catalytic oxidation catalyst has a specific surface area of 100-500, preferably 150-300m 2 / g.
[0029] In one aspect, the present invention provides the use of the above-mentioned VOCs catalytic oxidation catalyst in VOCs catalytic oxidation. The present invention has no specific restrictions on VOCs catalytic oxidation, and it can be carried out by conventional methods in the art. In one embodiment, the VOCs catalytic oxidation is carried out under the following conditions: VOCs are passed into a reactor filled with the VOCs catalytic oxidation catalyst, and the gas space velocity is 4000-25000h -1 , temperature is 150-450℃.
[0030] Example
[0031] The present invention will be described in detail below by way of examples. The examples are intended to illustrate but not to limit the present invention in any way.
[0032] Example 1
[0033] 10 g of attapulgite was added to 100 ml of 1 mol / L hydrochloric acid solution. The resulting mixture was stirred at room temperature for 1 hour, filtered, and dried at 100° C. to obtain acidified attapulgite. The acidified attapulgite was calcined in a muffle furnace at 300° C. for 2 hours to obtain pretreated attapulgite.
[0034] A 0.1 mol / L manganese nitrate solution and a 0.1 mol / L cerium nitrate solution were mixed in a volume ratio of 1:1 to form a non-precious metal salt solution. 2 g of pretreated attapulgite was added to 20 mL of the non-precious metal salt solution, and deionized water was added to a total volume of 50 mL. The mixture was evaporated to dryness at 80°C to obtain an impregnation product. The impregnation product was dried at 100°C for 12 hours and calcined at 400°C for 5 hours to obtain a catalyst precursor.
[0035] The catalyst precursor was mixed with 100 mL of 2 mol / L NaOH solution, stirred at 80° C. for 3 h, and centrifuged. The obtained solid was washed with deionized water until neutral, and dried at 100° C. to obtain Catalyst A.
[0036] Example 2
[0037] 10 g of montmorillonite was added to 100 ml of 1 mol / L hydrochloric acid solution. The resulting mixture was stirred at room temperature for 1 hour, filtered, and dried at 100° C. to obtain acidified montmorillonite. The acidified montmorillonite was calcined in a muffle furnace at 400° C. for 3 hours to obtain pretreated montmorillonite.
[0038] A 0.1 mol / L manganese nitrate solution and a 0.1 mol / L cobalt nitrate solution were mixed in a volume ratio of 2:1 to form a non-precious metal salt solution. 2 g of pretreated montmorillonite was added to 20 mL of the non-metal salt solution, and deionized water was added to a total volume of 50 mL. The mixture was evaporated to dryness at 80°C to obtain an impregnation product. The impregnation product was dried at 100°C for 12 hours and calcined at 550°C for 5 hours to obtain a catalyst precursor.
[0039] The catalyst precursor was mixed with 100 mL of 4 mol / L NaOH solution, stirred at 80° C. for 4 h, and centrifuged. The obtained solid was washed with deionized water until neutral, and dried at 100° C. to obtain Catalyst B.
[0040] Example 3
[0041] 10 g of kaolin was added to 100 ml of 2 mol / L hydrochloric acid solution. The resulting mixture was stirred at room temperature for 1 hour, filtered, and dried at 100° C. to obtain acidified kaolin. The acidified kaolin was calcined in a muffle furnace at 400° C. for 2 hours to obtain pretreated kaolin.
[0042] 0.3 mol / L cerium nitrate solution and 0.1 mol / L copper nitrate solution were mixed in a volume ratio of 1:1 to form a non-precious metal salt solution. 2 g of pretreated kaolin was added to 20 mL of the non-metal salt solution, and deionized water was added to a total volume of 50 mL. The mixture was stirred and evaporated to dryness at 80°C to obtain an impregnation product. The impregnation product was dried at 100°C for 12 hours and calcined at 500°C for 5 hours to obtain a catalyst precursor.
[0043] The catalyst precursor was mixed with 100 mL of 4 mol / L NaOH solution, stirred at 80° C. for 5 h, and centrifuged. The obtained solid was washed with deionized water until neutral, and dried at 100° C. to obtain Catalyst C.
[0044] Example 4
[0045] 10 g of attapulgite was added to 100 ml of 2 mol / L hydrochloric acid solution. The resulting mixture was stirred at room temperature for 1 hour, filtered, and dried at 100°C to obtain acidified attapulgite. The acidified attapulgite was calcined in a muffle furnace at 300°C for 2 hours to obtain pretreated attapulgite.
[0046] 0.2 mol / L manganese nitrate solution and 0.1 mol / L copper nitrate solution were mixed in a volume ratio of 1:1 to form a non-precious metal salt solution. 2 g of pretreated attapulgite was added to 20 mL of the non-metal salt solution, and deionized water was added to a total volume of 50 mL. The mixture was stirred and evaporated to dryness at 80°C to obtain an impregnation product. After the impregnation product was dried at 100°C for 12 hours, it was calcined at 500°C for 5 hours to obtain a catalyst precursor.
[0047] The catalyst precursor was mixed with 100 mL of 4 mol / L NaOH solution, stirred at 90° C. for 5 h, and centrifuged. The obtained solid was washed with deionized water until neutral, and dried at 100° C. to obtain Catalyst D.
[0048] Example 5
[0049] 10g of kaolin was added to 100ml of 1mol / L hydrochloric acid solution. The resulting mixture was stirred at room temperature for 1 hour, filtered, and dried at 100°C to obtain acidified kaolin. The acidified kaolin was calcined in a muffle furnace at 200°C for 2h to obtain pretreated kaolin.
[0050] 0.3 mol / L cerium nitrate solution and 0.1 mol / L cobalt nitrate solution were mixed in a volume ratio of 1:1 to form a non-precious metal salt solution. 2 g of pretreated kaolin was added to 20 mL of the non-metal salt solution, and deionized water was added to a total volume of 50 mL. The mixture was stirred and evaporated to dryness at 80°C to obtain an impregnation product. After the impregnation product was dried at 100°C for 12 hours, it was calcined at 550°C for 5 hours to obtain a catalyst precursor.
[0051] The catalyst precursor was mixed with 100 mL of 2 mol / L NaOH solution, stirred at 80° C. for 5 h, and centrifuged. The obtained solid was washed with deionized water until neutral, and dried at 100° C. to obtain Catalyst E.
[0052] Example 6
[0053] Add 10g of kaolin to 100ml of 1mol / L hydrochloric acid solution. The resulting mixture is stirred at room temperature for 1 hour, filtered, and dried at 100°C to obtain acidified kaolin. The acidified kaolin is calcined in a muffle furnace at 200°C for 2h to obtain pretreated kaolin. Add 10g of attapulgite to 100ml of 1mol / L hydrochloric acid solution. The resulting mixture is stirred at room temperature for 1 hour, filtered, and dried at 100°C to obtain acidified attapulgite. The acidified attapulgite is calcined in a muffle furnace at 200°C for 2h to obtain pretreated attapulgite.
[0054] 0.3 mol / L manganese nitrate solution and 0.1 mol / L cobalt nitrate solution were mixed in a volume ratio of 1:1 to form a non-precious metal salt solution. 1 g of pretreated kaolin and 1 g of pretreated attapulgite were added to 20 mL of the non-metal salt solution, and deionized water was added to a total volume of 50 mL. The mixture was stirred and evaporated to dryness at 80 ° C to obtain an impregnation product. The impregnation product was dried at 100 ° C for 12 h and calcined at 550 ° C for 5 h to obtain a catalyst precursor.
[0055] The catalyst precursor was mixed with 100 mL of 2 mol / L NaOH solution, stirred at 80° C. for 5 h, and centrifuged. The obtained solid was washed with deionized water until neutral, and dried at 100° C. to obtain Catalyst F.
[0056] Example 7
[0057] Add 10g of diatomaceous earth to 100ml of 1mol / L hydrochloric acid solution. The resulting mixture is stirred at room temperature for 1 hour, filtered, and dried at 100°C to obtain acidified diatomaceous earth. The acidified diatomaceous earth is calcined in a muffle furnace at 200°C for 2h to obtain pretreated diatomaceous earth. Add 10g of attapulgite to 100ml of 1mol / L hydrochloric acid solution. The resulting mixture is stirred at room temperature for 1 hour, filtered, and dried at 100°C to obtain acidified attapulgite. The acidified attapulgite is calcined in a muffle furnace at 200°C for 2h to obtain pretreated attapulgite.
[0058] 0.3 mol / L manganese nitrate solution and 0.1 mol / L copper nitrate solution were mixed in a volume ratio of 1:1 to form a non-precious metal salt solution. 1 g of pretreated diatomaceous earth and 1 g of pretreated attapulgite were added to 20 mL of the non-metal salt solution, and deionized water was added to a total volume of 50 mL. The mixture was stirred and evaporated to dryness at 80°C to obtain an impregnation product. The impregnation product was dried at 100°C for 12 h and calcined at 550°C for 5 h to obtain a catalyst precursor.
[0059] The catalyst precursor was mixed with 100 mL of 4 mol / L NaOH solution, stirred at 80° C. for 5 h, and centrifuged. The obtained solid was washed with deionized water until neutral, and dried at 100° C. to obtain Catalyst G.
[0060] Comparative Example 1
[0061] 0.1 mol / L manganese nitrate solution and 0.1 mol / L cobalt nitrate solution were mixed in a volume ratio of 2:1 to form a non-precious metal salt solution. 2 g of Al2O3 was added to 20 mL of the non-metal salt solution, and deionized water was added to a total volume of 50 mL. The mixture was stirred and evaporated to dryness at 80°C to obtain an impregnation product. The impregnation product was dried at 100°C for 12 hours and calcined at 550°C for 5 hours to obtain a catalyst precursor.
[0062] The catalyst precursor was mixed with 100 mL of 4 mol / L NaOH solution, stirred at 80° C. for 4 h, and centrifuged. The obtained solid was washed with deionized water until neutral, and dried at 100° C. to obtain Catalyst H.
[0063] Comparative Example 2
[0064] 0.3 mol / L manganese nitrate solution and 0.1 mol / L cobalt nitrate solution were mixed in a volume ratio of 1:1 to form a non-precious metal salt solution. 2 g of TiO2 was added to 20 mL of the non-metal salt solution, and deionized water was added to a total volume of 50 mL. The mixture was stirred and evaporated to dryness at 80 ° C to obtain an impregnation product. The impregnation product was dried at 100 ° C for 12 h and calcined at 550 ° C for 5 h to obtain a catalyst precursor.
[0065] The catalyst precursor was mixed with 100 mL of 2 mol / L NaOH solution, stirred at 80° C. for 5 h, and centrifuged. The obtained solid was washed with deionized water until neutral, and dried at 100° C. to obtain Catalyst I.
[0066] The catalysts of Examples 1-6 and Comparative Examples 1-2 were tested as follows:
[0067] The specific surface area of the catalyst was measured using a Micromeritics ASAP2020 adsorption instrument. The test results are summarized in Table 1.
[0068] The catalytic activity of the catalyst was tested as follows: the catalyst was loaded into a fixed bed reactor and a stream containing 2000 mg / m 3 Non-methane hydrocarbon VOCs simulated gas (including 200mg / m 3 Benzene, 600mg / m 3 Xylene, 600 mg / m 3 Para-xylene and 600mg / m 3 Methyl acetate), at a reaction temperature of 320°C and a volume space velocity of 10000 h -1 The reaction was carried out under the conditions of . The VOCs content in the outlet gas was detected by gas chromatography, and the test results are summarized in Table 1.
[0069] Table 1 Test results of catalysts of Examples 1-6 and Comparative Examples 1-2
[0070]
[0071]
[0072] The preferred embodiments of the present disclosure are described in detail above, but the present disclosure is not limited thereto. Within the technical concept of the present disclosure, the technical solution of the present disclosure can be subjected to a variety of simple modifications, including combining various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed herein and belong to the protection scope of the present disclosure.
Claims
1. A method for preparing a VOCs catalytic oxidation catalyst, comprising the following steps: impregnating a clay mineral with a non-precious metal salt solution, and performing a first drying and a first calcination on the impregnated product to obtain a catalyst precursor, wherein the amount of the clay mineral is 0.1-30wt%, preferably 1-20wt%, and more preferably 5-15wt% of the non-precious metal salt solution; and The catalyst precursor is etched with alkali to remove at least part of the clay minerals in the catalyst precursor to obtain a VOCs catalytic oxidation catalyst.
2. The method according to claim 1, wherein the clay mineral is one or more selected from montmorillonite, saponite, diatomite, kaolin, talc, illite, vermiculite, sepiolite, attapulgite, and serpentine; preferably one or more selected from montmorillonite, diatomite, kaolin, and attapulgite.
3. The method of claim 1, further comprising pretreating the clay mineral; Preferably, the pretreatment is pickling, heat treatment or both; Preferably, the acid is one selected from hydrochloric acid, sulfuric acid, and nitric acid, and the acid is used in an aqueous solution with a concentration of 0.1-10 mol / L, preferably 0.5-8 mol / L, more preferably 1-6 mol / L; Preferably, the heat treatment is carried out at 200-900° C., preferably 300-700° C., for 1-12 hours, preferably 2-8 hours.
4. The method of claim 1, wherein the non-precious metal is one or more selected from Cu, Co, Fe, Mn, Ce, Zr, La, Mg, Ti, Li, Na, K, Rb, Cs, Ca, Ba, Sr, Cr, Mo, W, Ni, Re, Zn, Cr, Ga, Al, Sn; Preferably, the non-precious metal salt is a nitrate of one or more non-precious metals selected from Cu, Co, Mn, Ce, and Zr; Preferably, the concentration of the non-precious metal salt solution is 0.01-5 mol / L, preferably 0.05-3 mol / L, and more preferably 0.08-1 mol / L.
5. The method of claim 1, wherein: The first drying is performed at 60-150° C. for 2-48 hours; and the first calcination is performed at 300-700° C., preferably 450-600° C., for 1-12 hours, preferably 2-8 hours.
6. The method according to claim 1, wherein the base is one or more selected from lithium hydroxide, sodium hydroxide, potassium hydroxide, and calcium hydroxide, preferably sodium hydroxide, potassium hydroxide, or both; Preferably, the base is used in an aqueous solution with a concentration of 0.1-10 mol / L, preferably 0.5-8 mol / L, more preferably 1-6 mol / L.
7. The method of claim 1, wherein etching the catalyst precursor with a base comprises the following steps: The catalyst precursor and the aqueous solution of the alkali are mixed in a water bath, stirred for 2-12 hours, and centrifuged to obtain a solid, which is then washed, dried, and calcined to obtain the VOCs catalytic oxidation catalyst.
8. A VOCs catalytic oxidation catalyst prepared by the method according to any one of claims 1 to 7.
9. Use of the VOCs catalytic oxidation catalyst according to claim 8 in the catalytic oxidation of VOCs.
10. The use of claim 9, wherein the catalytic oxidation of VOCs is carried out under the following conditions: VOCs are introduced into a reactor filled with the VOCs catalytic oxidation catalyst at a gas space velocity of 4000-25000 h -1 , temperature is 150-450℃.
Citation Information
Patent Citations
Preparation method and application of composite porous catalyst simultaneously containing titanium and other transition metals
CN113477252A
Honeycomb type Mn-Zn modified clay-based VOCs oxidation catalyst and preparation method thereof
CN107442108A
Ordered mesoporous gamma-MnO2 catalyst and preparation method and application thereof
CN109012656A
Kaolin-loaded vanadium catalyst for oxidative desulfurization, and preparation method and application thereof
CN110841625A
Composite metal oxide catalyst for catalytic combustion, and preparation method thereof
CN111036232A